If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2b + -5) = 2b Reorder the terms: -3(-5 + 2b) = 2b (-5 * -3 + 2b * -3) = 2b (15 + -6b) = 2b Solving 15 + -6b = 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 15 + -6b + -2b = 2b + -2b Combine like terms: -6b + -2b = -8b 15 + -8b = 2b + -2b Combine like terms: 2b + -2b = 0 15 + -8b = 0 Add '-15' to each side of the equation. 15 + -15 + -8b = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -8b = 0 + -15 -8b = 0 + -15 Combine like terms: 0 + -15 = -15 -8b = -15 Divide each side by '-8'. b = 1.875 Simplifying b = 1.875
| 19(3x-6)=25(x+2) | | -9h=-10h+10 | | 4r^2-16r-128= | | 125=8-3x | | 1.9=1.9-0.9x | | x/7-5=-11 | | -6m=-8-8m | | 6x+3x-5=49 | | -8r=10+2r | | 12x-20y=12 | | (2+3i)(x-iy)=3(x-2iy)+(2+i) | | -5+8x=2(14x+10)-x | | v+7=v | | -12x+7=-5 | | 9j-10=8j | | 14x+28-10x=8 | | (v^7)(v^2)= | | Tanx=0.44469726 | | 3+7x=2(4x+(-5))+x | | -3g+5=-3g | | 9-7x=7-4 | | X+6=3(5x-4) | | 90/4x3 | | X+32.7=-5.1 | | -9+10p=9p | | x/5-9=8 | | 3(x+5)=9(x+1) | | 2y-7-5y=-17 | | 2x+4=28+5x | | -9x+8=-19 | | 7x+1=8x+17 | | -9x-8=-19 |